Genetic diversity and variation among Akabane virus field isolates from goats in Yunnan, China - Wang, Jinping; Xin, Aiguo; He, Yuwen; Xie, Jiarui; Miao, Haisheng; Li, Fuxiang; Gao, Huafeng (Frontiers in Veterinary Science, 2025)
In China, the Akabane virus (AKAVs) has been reported in several host species. However, data regarding goats is still showing a gap. Akabane virus (AKAV) is an insect-borne virus from the Peribunyaviridae family that in ruminant species, particularly affects pregnant animals, resulting in abortions, stillbirths, and premature broth, often with congenital abnormalities. Therefore, there is a dire need to understand the diversity of this virus in ruminants, particularly in goats. The current study aimed to investigate the genotype characteristics of goat-originated AKAVs in Yunnan, China. For this, blood samples from goats were collected for four consecutive years (2019–2023) during routine disease surveillance in Yunnan province. The serum was harvested and evaluated for the seroprevalence of the AKAVs. The seroprevalence analysis revealed that the majority of goats in Yunnan province are infected with AKAVs, with a detected prevalence of 7.69% (92/1,197 tested), even though detected seroprevalence rose as high as 27.8% in some areas. For the evolutionary analysis of AKAVs of goat, five AKAVs strains were isolated from AKAV serum-positive goat blood samples were whole genome sequenced. The phylogenetic analysis (sequenced small and medium segments) classified the AKAVs into Ia and Ib genogroups, with Ia genogroup strains being more common in Yunnan goats. However, genotype II (TJ2016 and CQ-AKAV-1-2023) emerged in China. Overall, this study emphasizes the importance of implementing prevention and control strategies for AKAVs diseases transmitted in Yunnan, China.